A Phase-IV Non-interventional Study to Assess Virological Effectiveness, Safety, and Tolerability of DTG-based Antiretroviral Therapy in HIV-1 Infected Indian Persons Living with HIV - Ashta, Kuldeep K; Arora, Sumit; Khanna, Rajesh; Raman, Nishant; Anilkumar, Anirudh; Mohan, Charu (Current HIV Research, 2024)
BackgroundDolutegravir (DTG) is a novel yet preferential first- and -second-line treatment for persons living with HIV (PLH). Owing to its recent introduction, DTG-based regimens have not undergone a comprehensive, systematic evaluation regarding their real-world utilization and safety profile among a sizeable Indian population.ObjectiveThis study aimed to assess the 24 week immunovirological outcomes, anthropometric and metabolic changes, tolerability, and adverse events (AEs) of DTG-based antiretroviral (ART) regimens.MethodsA single-centre phase-IV non-interventional observational study involving 322 ART naïve and treatment-experienced PLH initiating DTG-based-regimens until October 2022 were followed up for outcomes at 24 weeks.ResultsAt 24 weeks, all PLH (n = 113) in the naïve group, all PLH (n = 67) in the first-line substitution group, 93.9% PLH (n = 46) in the first-line failure group, and 95.7% PLH (n = 89) in the second-line substitution group were virologically suppressed to plasma HIV-RNA <1000 copies/mL. Virological suppression rates to plasma HIV-RNA <200 copies/mL and <50 copies/mL were consistent among PLH who received DTG as first- or second-line ART.The mean-unadjusted weight gain observed was 3.5 kg (SE: 0.330), and it was significantly higher in PLH with poorer health at baseline (either HIV-RNA ≥ 1000 copies/ml or CD4 cell count <350 cells/µL). Overall, 27.3% PLH (n = 88) gained ≥10% of their baseline body weight, corresponding to 3.7% incidence (n = 12) of treatment-emergent clinical obesity. DTG had an overall lipid-neutral effect, with an advantageous effect being observed in PLH switching from non-nucleoside analogue reverse-transcriptase inhibitors (NNRTI) or ritonavir-boosted protease inhibitors (b/PI), especially in dyslipidemic pre-treated PLH (median change in total cholesterol: 28.5 mg/dL and triglycerides: 51 mg/dL), possibly emanating from the withdrawal of the offending ART. The incidence of DTG-specific AEs, including CNS AEs, was low. Two PLH developed proximal myopathy and one developed transaminitis, warranting DTG discontinuation. Asymptomatic serum-CPK elevation and drug-induced transaminitis were seen in 25.2% (n = 27) and 3.2% (n = 10) PLH, respectively. No apparent negative effects on renal function were detected.ConclusionOur results from a large Indian cohort indicate a favourable virological and metabolic response, with good tolerance of DTG-based ART at 24 weeks.
Keywords: dolutegravir